Teachers’ digital literacy overview in secondary school - Sherly Rahmawati; Ade Gafar Abdullah; Isma Widiaty (Institute of Advanced Engineering and Science, 2024)
This study explored the teachers’ digital literacy in secondary school and deciphered the most suggested way of enhancing secondary teachers’ digital literacy, overview levels, and the trends factors in the last five years of research. The methodologies in this study employed the traditional systematic literature review (SLR), which compiled some previous studies to be examined. The initial studies were only selected from an article published in a reputable journal indexed by Scopus. Of the 118 articles reviewed, 46 were selected to be included in the analysis. Significant findings summarize the fact that most of the last five-year research about teachers in secondary schools was impacted by the rapid development of technology and the demand for 21st-century skills. To summarize, as it is at the intermediate level, most secondary school teachers are digitally literate. However, future research may evaluate digital literacy training programs for teachers to assess what improvements should be made to delivery as well as existing frameworks used to test teachers’ digital literacy.